The hard truth about hardware in cyber-security: it's more important. Issue 12 (December 2016) - Wagner, Mathias
Abstract : When it comes to cyber-security, there is currently an emphasis on the need for software to be secured, while hardware appears to have taken a back seat. However, a recent Kaspersky report showed that 92% of hosts connected to Industrial Control Systems (ICS) contained vulnerabilities that can be exploited to attack, take over or even harm devices and their normal mode of operation. 1